“A Real China” on User-Generated Videos? Audio-Visual Narratives of Confucianism - Jianxiu Hao (tripleC: Communication, Capitalism & Critique)
Beneath the “Chinese successful story”, social stratification, class polarization, and cultural displacement have been accelerated. The Chinese Communist Party has not found a coherent solution to the challenges of reconciling social interests, since Communism has been more and more becoming mere “lip service”. However, it has been claimed that Confucian values can provide sources to dissolve the downsides of modernization in contemporary Chinese society. This study intends to investigate the revival of Confucianism, as a source for criticism and construction in Chinese socio-culture, as portrayed in user-generated videos which are produced/consumed by the largest Internet using population in the world, under the Chinese authoritarian regime which controls over communication. By means of a thematic audio-visual narrative analysis, this study has investigated 20 hours of Youku Paike videos published between 2007 and 2013. It has been detected:  (1) about one third of the user-generated videos can be interpreted as Confucian thematic narratives; and there is a slightly increasing trend portraying Confucian values; (2) Confucianism can become a source for the formation of a new online socio-culture, in the circumstances of China’s modernization and cyberization, to advocate social actors’ cultivation and humanity’s flourishing.